COSMOPOLITANISM, MODERNITY, AND CULTURAL DYNAMICS: PERSPECTIVES FROM KERALA, INDIA - Hemanth M (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Kerala as a state in India is popular for its human development index comparable with many of the European countries. Kerala’smodel of developmenthas grabbed the attention of academicians all across the world.Neither agrarian nor industrial, the economic growth model of Kerala is a unique phenomenon, where cross-cultural interactions played a quintessential role. The amalgamation of modern Enlightenment thoughts along with the traditional values together contributed in shapingthissociety,where cosmopolitanismemerged asa predominant approach and outlook. Cosmopolitanism in Kerala is a highly complex culturalprocess,which playsa rudimentary role in the holisticgrowth that it attains in multiple domains of social life.This study aims to critically trace the historical roots of cosmopolitanism, cross-cultural interactions, and to further analyze how it has fundamentally moulded the modernity of Kerala.